Experiencing abstraction: On mega-events, liminality, and resistance - Pavoni, A. (Liminality and critical event studies: Borders, boundaries, and contestation, 2020)
This chapter explores liminality vis-à-vis mega-events (MEs) and neoliberal urbanisation, proposing MEs as opening a liminality which remains un-experienced. MEs are not simply phenomenologically liminoid but ontologically liminal space-times through which neoliberal urbanisation contradictorily occurs: consistent with Jameson’s definition of modernity as a disjunction between experience and abstraction. Not the confusing experience of a liquefaction that is not dialectically resolved into order then (cf. Szakolczai), modern liminality should be understood as the aesthetic fracture between experience and the forces that order the conditions of experience itself. Critiquing urban capitalism must be completed by an eminently aesthetic perspective: not the romantic attempt to restore an authentic experience of communitas against neoliberal eventification, but of making experienceable, those phenomena which shape our being in the world.